Technical efficiency in small and medium-sized firms in Mexico: A stochastic frontier analysis - Basurto Hernández, Saúl; Sánchez Trujillo, Gabriela (Estudios Económicos de El Colegio de México, 2022)
This paper examines the knowledge-technical efficiency (TE) association in small and medium-sized enterprises (SMEs) of manufacturing, trade, and service sectors. We use data from 2014 and 2017 reported by 28,034 SMEs in the National Survey on Productivity and Competitiveness of Micro, Small and Medium Enterprises (Encuesta Nacional sobre Productividad y Competitividad de las Micro, Pequeñas y Medianas Empresas, ENAPROCE) and the Stochastic Frontier Analysis (SFA). The main findings suggest that the average technical efficiency (ATE) of SMEs is 54.6%, SMEs show decreasing returns to scale, and SMEs with highly skilled workers -that transfer their technology less frequently and that use the Internet in their production processes- tend to have higher levels of TE. On the other hand, those firms that spend a higher proportion of their revenues on the process of paying taxes tend to be less efficient than others.